Exchange-driven all-optical magnetic switching in compensated 3d ferrimagnets - Stamenov, Plamen; Coey, John; Rode, Karsten (My University, 2020)
Understanding how a single laser pulse can toggle magnetization in a compensated 3d ferrimagnet is a critical problem in ultrafast magnetism. To resolve it, we test single-shot all-optical switching of magnetization in Mn 2 Rux Ga at different temperatures using femto- to picosecond pulses in the visible to far-infrared spectral ranges. The switching process is found to be independent of photon energy, but strongly dependent on both the pulse duration and sample temperature. Switching is disabled whenever the starting temperature T0 is above the compensation point of Mn 2 Rux Ga, but as T0 is lowered below compensation, increasingly longer pulses become capable of toggling the magnetization. We explain the observations in terms of a switching process driven by exchange relaxation of the angular momenta of the manganese sublattices, and propose a common framework to account for the similarities and differences of all-optical switching in Mn 2 Rux Ga and GdFeCo alloys.
PUBLISHED
Keywords: magnetization; single laser pulse; single-shot all-optical switching of magnetization